Penerapan Massage Abdomen untuk Menurunkan Volume Residu Lambung pada Cronic Kidney Disease (CKD) di Ruang Intensive Care Unit - Fransiska Fajar Mulyaningsih; Dheni Koerniawan; Vincencius Surani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Chronic Kidney Disease (CKD) is a structural or functional abnormality of the kidneys that lasts ≥3 months with the criteria of eGFR <60 mL/min/1.73 m² or the presence of kidney damage such as albuminuria and urinary abnormalities (Kidney International, 2024). CKD patients, especially those treated in intensive care units, often experience gastrointestinal disorders such as increased volume of gastric residues. Giving enteral nutrition to patients with NGT can increase the volume of gastric residue which is at risk of causing complications. One of the non-pharmacological interventions that can be carried out is abdominal massage, which is a light massage technique in the abdominal area that can stimulate intestinal peristalsis and improve gastrointestinal motility. The purpose of this case study was to determine the effect of giving abdominal massage on reducing the volume of gastric residue in CKD patients in the ICU. This scientific paper uses a case study design using abdominal mass therapy. The number of respondents was 3 people, the intervention was carried out for 3 days with a time of 10-15 minutes. The application of abdominal massage therapy in the three respondents showed a decrease in the volume of gastric residue after admixture was carried out for three consecutive days with an average decrease in the volume of gastric residue, which was 50 cc - 75 cc. Abdominal massage is a safe and effective nonpharmacological nursing intervention to help reduce gastric residue volume and support enteral nutrient tolerance in CKD patients in the ICU.